EVLAUASI PROGRAM PEMBERIAN F100, SIROP BESI DAN PEMBERIAN MAKANAN TAMBAHAN (PMT) PADA BALITA GIZI BURUK DI WILAYAH KERJA PUSKESMAS REMBANG 2 - Ade Risma Febriyanti; Oktia Woro Kasmini Handayani (Jurnal Kesehatan Masyarakat, 2022)
Based on Riskesdas 2018, the proportion of undernutrition and malnutrition nationally is 17.7%. While in the RPJM 2019 is 17% and RPJM 2020-2024 is 7%. Malnourished children under five years in Rembang Regancy in 2018 was ranked 7th , namely 8.4%. Meanwhile at Rembang 2 health care center in 2020 there were 0.93% and 2021 1.37% malnutrition children. One of the program to resolve malnourised is F100, Iron Syrup and Suplementary Feeding Program. The purpose of the study was to evaluate of  F100, Iron Syrup and Suplementary Feeding Program for malnourished children under five years in  Rembang 2 Health Care Center using the context, input, prosess, and product (CIPP) method. The research was qualitative with descriptive approach. Informants were selected by purposive sampling consisting of 4 main informants and 5 triangulated informants. Data collection techniques with in-depth interviews and documentation. The instruments used are observation guidelines, interview guidelines, recording devices, and cameras. Analysis data used are data collection, data reduction, data display, and drawing conclutions. The result the implementation of the program with CIPP component had not run optimally and there are discrepancies with the guidelines, such as in determining the target children under five years using BB/U index, limited human resource, lack of parental role, and recepvity low of food in children. The F100, Iron Syrup and Suplementary Feeding Program (PMT) seen form context, input, process and product (CIPP) have problems that still need to be fixed, so the program would be maximal.